Ion implantation process of Lanthanum and Titanium Dopants into a substrate of FE80 CR20 - Hendi, Saryanto; Darwin, Sebayang; Pudji, Untoro; Tjipto, Sujitno (Universiti Malaysia Perlis, 2010)
Organized by School of Materials Engineering & Sustainable Engineering Research Cluster, 1st - 2nd December 2009 at Putra Brasmana Hotel, Kuala Perlis, Perlis.